The effect of eccentric training on tissue repair in individuals with Achilles tendinopathy: a literature review - Souza, Rafael Virgínio de; Araújo, Vanessa Lara (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The tendinopathy is a common dysfunction in athletes and its numbers has increased in the last few years. Regarding tendon lesions, the Achilles tendinopathy is one of the most commons, especially among runners. There are several techniques to treat tendon lesions, such as the eccentric exercise. This exercise is widely used and discussed in the literature. Objective: To carry out a literature review in order to investigate the short and long term effects of eccentric exercise on tendon vascularization and structure in patients with Achilles tendinopathy. Methods: A literature search was performed in the PubMed, Scielo, Lilacs and PEDro databases. Results: 13 studies that measure the effects of eccentric exercises in the tendon structure were selected. Conclusion: The studies suggest that eccentric exercise can modify tendon structure in short and long term, reestablishing its healthy structure conditions.